Al-Muwaththa': Karya Agung Imam Malik yang Mengubah Dunia Islam - Jayus, Muhammad; Khairuddin; Irham, Muhammad (Institut Agama Islam Darul Fattah Lampung, 2024)
This research analyzes Al-Muwaththa’, a monumental work by Imam Malik bin Anas, as one of the pivotal books in shaping Islamic law and the dissemination of the Maliki school of jurisprudence in the Islamic world. As a compilation of hadith compiled with a rigorous methodology, Al-Muwaththa’ not only serves as a source of law but also offers a contextual perspective by using the practices of the people of Medina (amal ahl al-Madinah) as one of the legal bases. The main problem discussed in this research is how Al-Muwaththa’ has influenced the development of Islamic law and the relevance of its methodology for Muslim communities in various regions, especially in the context of local cultural adaptation. Through a qualitative approach with a literature review, this research examines Imam Malik's methodology in selecting hadith, integrating ra'y (legal opinion) with traditional sources, and structuring the book based on legal categories. The results of the analysis show that Al-Muwaththa’ has successfully become the basis for the formation of the Maliki school of jurisprudence, which is widely spread in regions such as North Africa and Andalusia. Imam Malik's approach, which combines the chain of transmission of hadith and local practices, provides flexibility in the continuous application of Islamic law. In addition to being recognized as a valid legal reference by great scholars such as Imam Shafi'i, Al-Muwaththa’ also serves as a model for the development of other Islamic law books. The prospect is that the contextual methodology introduced by Imam Malik in Al-Muwaththa’ can continue to be studied as inspiration for adapting Islamic law to modern cultural and social contexts without leaving the essence of religious teachings.